General stress response to conventional and laparoscopic cholecystectomy - Glaser, Florian; Sannwald, Gerd A.; Buhr, Heinz J.; Kuntz, Christian; Mayer, Horst; Klee, Fritz; Herfarth, Christian (Annals of surgery, 1995)
Objective - In many retrospective and prospective observational studies, laparoscopic cholecystectomy (LC) compares favorably with conventional cholecystectomy (CC), with respect to length of hospital stay, postoperative pain, and pulmonary function, indicating a diminished operative trauma. Comparison of laboratory findings (stress hormones, blood glucose, interleukins) are a possibility to objectify stress and tissue trauma of laparoscopic and conventional cholecystectomy. - Summary Background Data - Major body injury, surgical or accidental, evokes reproducible hormonal and immunologic responses. The magnitude of many of these changes essentially is proportional to the extent of the injury. - Methods - In a prospective study, biochemical stress parameters were measured in the blood of patients undergoing elective cholecystectomy because of symptomatic cholecystolithiasis. Patients with acute cholecystitis, pancreatitis, choledocholithiasis, or malignant disease were excluded. Values from 40 patients after LC and from 18 patients after CC were compared. Both groups had similar patient characteristics, baseline values, and perioperative care, except for deeper anesthesia during CC. - Results - On postoperative day 1, epinephrine (p = 0.05), norepinephrine (p = 0.02), and glucose (p = 0.02) responses were higher after CC. Two days postoperatively, norepinephrine remained higher after CC (p < 0.01). Interleukin-1β responses were higher during (p < 0.01) and 6 hours after CC (p = 0.03). Interleukin-6 responses were higher 6 hours (p = 0.03), 1 day (p = 0.02), and 2 days (p < 0.01) after CC. - Conclusions - The results show significant lower values of intraoperatively and postoperatively measured epinephrine, norepinephrine, interleukin-1β, and interleukin-6 in patients with laparoscopic cholecystectomy, indicating a minor stress response and tissue trauma in this group of patients. The results correspond to the favorable results of most other trials evaluating clinical aspects of laparoscopic cholecystectomy.